pH-induced in situ gelling system of an anti-infective drug for sustained ocular delivery - Abdul Malik PH and S Satyananda (Journal of Applied Pharmaceutical Science, 2014)
Recently, in situ gel formation has been extensively studied to enhance ocular bioavailability and the duration of drug activity. Poor ocular bioavailability of drugs (
Keywords: pH induced in situ gel, Gatifloxacin, Carbopol 940, HPMC E50LV, HPMC E4M.